Clinical significance of the serum miR-455-5p expression in patients with neonatal sepsis. Issue 1 (1st January 2021) - Mao, Yue-Yan; Su, Chang; Fang, Cheng-Chao; Fan, Xiao-Ping; Wang, Li-Ping; Zhu, Shan-Shan; Yao, Hai-Ming
ABSTRACT: Sepsis is a systemic inflammatory response caused by infection and is a major cause of neonatal death. This study explored the miR-455-5p in neonatal sepsis, and further investigated the diagnostic and prognostic value of miR-455-5p in neonatal sepsis (NS). The levels of serum miR-455-5p in 88 healthy controls and 90 NS patients were examined by quantitative real-time polymerase chain reaction (qRT-PCR). Pearson correlation coefficient was used to evaluate the correlation between miR-455-5p and clinical features. Receiver operating characteristic (ROC) curve analysis was performed for the diagnostic evaluation on miR-455-5p. The prognostic value of miR-455-5p in NS was analyzed by Kaplan–Meier survival curve and multivariate Cox regression. The expression of serum miR-455-5p in NS patients was highly expressed in comparison to healthy controls ( P < 0.001), and the level of miR-455-5p was positively correlated with white blood cell count (WBC) and other clinical characteristics ( P < 0.01). The AUC value of ROC curve was 0.895, suggesting that miR-455-5p had diagnostic value for NS. Survival analysis illustrated that patient with high miR-455-5p expression had poor prognosis (log rank P = 0.015), and miR-455-5p may be a potential prognostic marker for NS (HR = 3.454, 95% CI = 1.165–10.234, P = 0.025). The expression of miR-455-5p had the ability to distinguish NS from healthy people, and highly expressed miR-455-5p was associated with poor prognosis in NS patients. GRAPHICAL ABSTRACT: uf0001